2013
DOI: 10.4171/jncg/144
|View full text |Cite
|
Sign up to set email alerts
|

Calabi-Yau pointed Hopf algebras of finite Cartan type

Abstract: Let k be an algebraically closed field. The main goal of this paper is to classify the finite-dimensional pointed Hopf algebras over k of finite corep-resentation type. To do so, we give a necessary and sufficient condition for a basic Hopf algebra over k to be of finite representation type firstly. Explicitly, we prove that a basic Hopf algebra over k is of finite representation type if and only if it is Nakayama. By this conclusion, we classify all finite-dimensional pointed Hopf algebras over k of finite co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Chelma showed that the algebras U q (g) are CY algebras [11,Theorem 3.3.2]. The CY property of the algebras U (D, λ) were discussed in [39]. In this section we will show that the cleft objects of the algebras U (D, λ) are all twisted CY algebras.…”
Section: Cleft Objects Of U (D λ)mentioning
confidence: 84%
See 3 more Smart Citations
“…Chelma showed that the algebras U q (g) are CY algebras [11,Theorem 3.3.2]. The CY property of the algebras U (D, λ) were discussed in [39]. In this section we will show that the cleft objects of the algebras U (D, λ) are all twisted CY algebras.…”
Section: Cleft Objects Of U (D λ)mentioning
confidence: 84%
“…(iii)The algebra H is CY if and only if p i=1 χ β i = ε and S 2 is an inner automorphism.Proof. (i) This is Theorem 2.2 in[39].…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…For example, those Hopf algebras in the classification of Calabi-Yau pointed Hopf algebras of finite Cartan type in [23].…”
Section: Proposition 41 Suppose That a Is A Koszul As-regular Algebmentioning
confidence: 99%